2001
DOI: 10.1128/mmbr.65.3.390-403.2001
|View full text |Cite
|
Sign up to set email alerts
|

Questionable Thymic Nurse Cell

Abstract: Since their discovery in 1980, thymic nurse cells (TNCs) have been controversial. Questions pertaining to the existence of the TNC as a “unit” cell with thymocytes completely enclosed within its cytoplasm were the focus of initial debates. Early skeptics proposed the multicellular complex to be an artifact of the procedures used to isolate TNCs from the thymus. Since that time, TNCs have been found in fish, frogs, tadpoles, chickens, sheep, pigs, rats, mice, and humans. Their evolutionary conservation througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…TNC is defined as a large epithelial cell that completely envelops many viable lymphoid cells within its intracellular vesicles (7)(8)(9)(10). Despite the initial suggestion that TNC may be important for T-cell development and selection, its in vivo existence has been questioned and its function has remained unclear (10,19,20). The present results, including the analysis of the intravital imaging results of β5t + cTECs, reveal that basketlike globular cTECs, including closed TNC complexes, are indeed present in the thymic cortex in situ and are not merely artificial structures formed during cell preparation.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…TNC is defined as a large epithelial cell that completely envelops many viable lymphoid cells within its intracellular vesicles (7)(8)(9)(10). Despite the initial suggestion that TNC may be important for T-cell development and selection, its in vivo existence has been questioned and its function has remained unclear (10,19,20). The present results, including the analysis of the intravital imaging results of β5t + cTECs, reveal that basketlike globular cTECs, including closed TNC complexes, are indeed present in the thymic cortex in situ and are not merely artificial structures formed during cell preparation.…”
Section: Discussionmentioning
confidence: 49%
“…It was further hypothesized that the TNC complex is a site for the positive and negative selection of T cells (16)(17)(18). However, how TNCs are involved in T-cell development, and selection has not been established (19). Whether TNCs are abundant in the thymic cortex (10) or derived from all parts of the thymus including the medulla (20) has not been clarified as well.…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of m17TLP is confirmed to a subset of TNC. As TNC have been found in two different areas of the thymus (reviewed in [33]), the outer cortex and the cortico-medullary junction, one may hypothesize that only the subset found at the cortico-medullary junction expresses m17TLP. Another explanation is that m17TLP is restricted to a particular developmental stage of TNC.…”
Section: Discussionmentioning
confidence: 99%
“…A particular microenvironment of the thymus is formed by 2 cell types, thymic nurse cells (TNC), a TEC subtype, and immature thymocytes [for a review, see 15,16] . These complexes were first described in 1980 by Wekerle et al [17] and are observed both after isolation and in thymic sections [18,19] .…”
Section: Objectivementioning
confidence: 99%